Research on electromagnetic vibration and noise of transformer under short circuit conditions - Zhongxiang Li; Wenxing Sun; Duanjiao Li; Dezhi Chen; Linglong Cai; Xian Yang; Shuo Jiang; Ziyuan Xin; Xianghui Chang; Sunjing Gong (AIP Advances)
For an open-type 50 kV A three-dimensional laminated core transformer, this paper establishes a research framework for inter-turn short-circuit faults from the perspective of the power system. First, the B–H curve and magnetostriction curve of the silicon steel sheets were measured using a single-sheet silicon steel magnetostriction measurement system, providing data support for electromagnetic, vibration, and noise analysis. Based on finite element analysis, electromagnetic and vibration characteristics of the three-dimensional laminated core transformer were simulated and analyzed, establishing a steady-state model and verifying its validity. Second, an equivalent circuit model and a finite element model for the transformer winding under inter-turn short-circuit conditions were established. Simulations were conducted to analyze current, leakage magnetic field, and electrodynamic forces. Through simulation, the effects of different short-circuit timings on the transformer’s status were examined, revealing the size and distribution of axial and radial leakage magnetic fields, as well as axial and radial electrodynamic forces under different numbers of shorted turns. Finite element simulation software was used to calculate the magnetic field, vibration, and noise in the three-dimensional laminated core transformer following an inter-turn short circuit. This study delves into the magnetic field, vibration, and noise during normal operation and under varying numbers of shorted turns, analyzing the impact of inter-turn short circuits on the performance and stability of the transformer.